The feasibility of colorectal endoscopic submucosal dissection for the treatment of residual or recurrent tumor localized in therapeutic scar tissue - Kobayashi, Ryosuke; Hirasawa, Kingo; Ikeda, Ryosuke; de Fukuchi, Takeh; Ishii, Yasuaki; Kaneko, Hiroaki; Makazu, Makomo; Sato, Chiko; Maeda, Shin (Endoscopy International Open, 2017)
Background and study aims Endoscopic submucosal dissection (ESD) is used to treat superficial colorectal tumors. Previous studies have reported the efficacy of ESD for treating residual or local recurrent colorectal tumors. This study sought to evaluate the efficacy of ESD in treating these lesions and to assess factors that prevent successful ESD.Methods This retrospective study assessed 25 cases of residual or local recurrent lesions that were previously treated using EMR (18 lesions), TEM (5 lesions), ESD (1 lesion) or surgery (1 lesion), and 459 primary lesions treated using ESD between April 2008 and September 2015. Clinicopathological characteristics, treatment outcome and adverse events were compared between groups with or without scar tissue. Factors related to perforation and a prolonged treatment time, which indicate the likelihood of technical difficulties, were identified using multiple logistic regression analysis.Results In residual or local recurrent lesions groups, patients experienced more perforations (32 % vs 4 %, P < 0.001) and required a longer treatment time (117 min vs 61 min, P < 0.001) compared with the primary lesions group. Both groups showed a similar curative resection rate. Emergency surgery was not needed in any case. Multiple logistic regression analysis indicated that tumor location and therapeutic scar tissue were high risk factors for perforation, and that large tumor size and therapeutic scar tissue were high risk factors for prolonged treatment time.Conclusions ESD for residual or local recurrent colorectal tumors is a technically challenging, but effective and minimally invasive treatment. When performed carefully with sufficient proficiency, it is a useful treatment option.